Combination of physical activity and screen time on life satisfaction in adults: A cross-sectional survey - Chen, Zhenhuai; Sun, Jiangang; Zhuang, Wei (Frontiers in Psychology, 2022)
Abstract: Little is known about the association between combinations of physical activity and screen time and life satisfaction in adults. This study aimed to fill the research gap in the literature. The 2014 European Social Survey data was used to achieve the study aim. Self-reported questionnaire was used to collect data on physical activity, television viewing time and life satisfaction as well as other sociodemographic information. Physical activity and television viewing time was grouped into meeting the recommendations (physical activity: 7 days or not; television viewing time: more than 3 hours or not per day), respectively. Participating in more physical activity and watching more television was positively and negatively associated with life satisfaction, respectively. Meeting the physical activity recommendations in insolation was more likely to report higher life satisfaction scores (odds ratio = 1.22, 95%CI: 1.11-1.34); meeting the screen time recommendations in insolation was inclined to report higher life satisfaction scores (odds ratio = 1.26, 95%CI: 1.14-1.40). Meeting both physical activity and screen time recommendations had a higher odds ratio (odds ratio = 1.54, 95%CI: 1.36-1.76) compared with meeting neither of the guidelines and was also higher than that of meeting either of the guidelines. This study stressed the importance of engaging in sufficient physical activity and limiting screen time in adults, for which help this population gain health benefits.